Teaching the balanced scorecard through simulation - Lopes, A.I.; Capelo, C.; Mata, A. (Proceedings of the IADIS International Conference on Cognition and Exploratory Learning in the Digital Age 2012, 2012)
Kaplan and Norton introduced the Balanced Scorecard (BSC) which is based on a systems perspective of the business strategy and performance measurement. Many organizations around the world are using the BSC to define, implement and manage strategy. Nevertheless there exist studies that identify problems and limitations associated with the implementation and use of the BSC. Those studies show in general terms that managers do not understand the BSC as the measures and perspectives in use are fairly independent, and do not always mirror the recommended cause-and-effect logic included in the systems perspective of the BSC approach. This article addresses the effectiveness of teaching the Balanced Scorecard by means of business simulation. An experiment that uses a business simulator is performed for testing a set of hypotheses about the influence of simulation on the students’ understanding of the BSC. The simulation experience was specifically designed by the authors to promote understanding of the BSC concepts. Student feedback and assessment showed that the simulation significantly enhanced the understanding of the BSC concepts related to the strategic management and double-loop learning processes and the systems perspective. Results also suggested that understanding of those BSC concepts positively influences simulation performance.